Peran Guru dalam Meningkatkan Pendidikan Budi Pekerti Pada Siswa Kelas IV di SD Inpres Titigogoli - Atter Raraga (Peneliti.net, 2020)
The aim of this research is to see 1) the shape of the character of the students at SD Inpres Titigogoli. 2). character building for students carried out at SD Inpres Titigogoli. 3). what strategies are used in ordering the character of students at SD Inpres Titigogoli. 4). teacher implementation of the principal's program on realizing good student character at SD Inpres Titigogoli. This type of research used in this research is qualitative research. The results in this study are, 1). The shape of the character of each student is different, but from that difference how a teacher who is able to maintain it, is still awake and still bad then it is repaired or nurtured to be even better. 2). Character building carried out in schools is a national movement to create schools that foster ethical, responsible, and caring young generations through modeling and teaching good character with universally agreed upon universal assessments. But we need to remember, that to build character in a student, all parties must be involved, be it the community, the environment, the school and the important thing is the interests of the family. 3). The strategy that the teacher uses in shaping student character is very good through integration, through daily activities that include: presenting exemplary, admonition, advice, and environmental conditioning that support character education. 4). In its application to the character values ​​implemented by teachers to students at SD Inpres Titigogoli it has been good but has not been maximally implemented.